Alcohol and alcohol-related diseases - Mueller, Sebastian; Heilig, Markus (Springer Nature, 2023)
Alcohol and Alcohol-related Diseases: An Introduction to the Book -- I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects I Alcohol consumption: Epidemiology, policies and legal aspects II Alcohol addiction: Introduction and diagnosis Alcohol addiction: Introduction and diagnosis II Alcohol addiction: Introduction and diagnosis II Alcohol addiction: Introduction and diagnosis III Treatment of alcohol addiction Treatment of alcohol addiction III Treatment of alcohol addiction III Treatment of alcohol addiction III Treatment of alcohol addiction III Treatment of alcohol addiction III Treatment of alcohol addiction III Treatment of alcohol addiction Fetal Alcohol Spectrum Disorders (FASD) IV Fetal Alcohol Spectrum Disorders (FASD) IV Fetal Alcohol Spectrum Disorders (FASD) Structural and functional central nervous system pathology in alcohol addi V Structural and functional central nervous system pathology in alcohol addi V Structural and functional central nervous system pathology in alcohol addi V Structural and functional central nervous system pathology in alcohol addi V Structural and functional central nervous system pathology in alcohol addi V Structural and functional central nervous system pathology in alcohol addi VI Risk factors for Alcohol Addiction and Lessons from Basic Science Risk factors for Alcohol Addiction and Lessons from Basic Science VI Risk factors for Alcohol Addiction and Lessons from Basic Science VI Risk factors for Alcohol Addiction and Lessons from Basic Science VI Risk factors for Alcohol Addiction and Lessons from Basic Science VII Alcohol-related liver disease: Diagnosis Alcohol-related liver disease: Diagnosis VII Alcohol-related liver disease: Diagnosis VII Alcohol-related liver disease: Diagnosis VII Alcohol-related liver disease: Diagnosis VII Alcohol-related liver disease: Diagnosis Medical aspects of alcohol consumption and alcohol-related liver disease VIII Medical aspects of alcohol consumption and alcohol-related liver disease VIII Medical aspects of alcohol consumption and alcohol-related liver disease VIII Medical aspects of alcohol consumption and alcohol-related liver disease VIII Medical aspects of alcohol consumption and alcohol-related liver disease -- Epidemiology of Alcohol and Opioids Epidemiology of Alcohol-related Liver Disease in Europe Epidemiology of Alcohol-related Liver Disease in Romania Epidemiology of Alcohol-related Liver Disease in China Epidemiology of Alcohol-related Liver Disease in Russia Alcohol and mortality: First Preliminary Lessons from a Prospective 15 year Follow-up Study#xa0; Legal aspects of alcohol intake: A Romanian perspective COVID-19 and Alcohol Use Disorder The Principles of Policies to Reduce the Burden of Liver Disease Medical Treatment of Alcohol use Disorder: A Multidisciplinary Approach Diagnosis of Alcohol use Disorder and Identification of Unhealthy Alcohol Consumption#xa0; State Markers of Alcohol Use and their Application Addictions Neuroclinical Assessment Evidence-based Behavioral Treatments Approved, Promising, and Experimental Medications for Treatment of Alcohol Use Disorder#xa0; Comorbidity with substance use disorders and/or psychiatric disorders Treatment of Adolescents Transcranial Magnetic Stimulation in Addiction Therapies The Clinical Benefits of Non-Abstinent Outcomes in Alcohol Use Disorder Treatment: Evidence from Clinical Trials and Treatment Implications; Laboratory Based Approaches To Medications Development For Alcohol Addiction Emergency Room: Acute Alcohol Intoxication and Other Alcohol-related Acute Problems Including Alcohol Withdrawal Syndrome Introductory comments on FASD and the Collaborative Initiative on FASD Image Analysis of Neurofacial Effects of Prenatal Alcohol Exposure From Surviving to Thriving”: A Focused Review of Interventions for Fetal Alcohol Spectrum Disorders to Guide a Shift Toward Strengths-Based Intervention Development. Structural and Functional Imaging of Alcohol’s Effects on the Brain Brain Microstructure in Alcohol Addiction: Characterization of Diffusion-based MRI Biomarkers, Neuropathological Substrates, and Functional Consequences Determinants of Risk Developmental Trajectories for Risky and Harmful Alcohol Use: Lessons from the IMAGEN Consortium Impulsivity and Alcohol Use Disorder Brain-Immune Mechanisms in Alcohol Use Disorder Targeting Neuroimmune Signaling in Alcohol Use Disorder: Opportunities for Translation Brain Alterations and Cognitive Deficits Induced by Alcohol Use Disorder The Genetics of Alcohol Use Disorder Alcohol Responses as Phenotypic Markers of AUD Risk - Lessons from Longitudinal Studies#xa0; Early Life Adversity as a Risk Factor in Alcohol Addiction Animals Models Used to Study Alcohol Use Disorder Alcohol Use Disorder: Stress, Negative Reinforcement, and Negative Urgency Laboratory Parameters in Heavy Drinkers Histology of Alcohol-related Liver Disease Non-Invasive Fibrosis Assessment in Alcohol-Related Liver Disease Noninvasive Biomarker Screening and Alcohol-Related Liver Disease in the General Population Evidence for Red Blood Cell-derived Aspartate Aminotransferase in Heavy Drinkers#xa0; Fibrosis Screening of Alcohol-related Liver Disease Based on Elastography Portal Hypertension in ALD The impact of alcohol components in ulcerative colitis and Crohn's disease Coagulation Disorders in Patients with Alcoholic Liver Cirrhosis Hepato-renal Syndrome in Patients with Alcohol-related#xa0;Liver Disease Acute Liver Failure Due to Alcohol Intoxication- therapeutic Options Medical aspects of alcohol consumption and alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease IX Molecular mechanisms of of alcohol-related liver disease X Severe alcoholic hepatitis Severe alcoholic hepatitis X Severe alcoholic hepatitis X Severe alcoholic hepatitis X Severe alcoholic hepatitis Alcohol-related damage of other organs XI Alcohol-related damage of other organs XI Alcohol-related damage of other organs XI Alcohol-related damage of other organs XII Alcohol and cancer Alcohol and cancer XII Alcohol and cancer Center experiences for the interdisclipninary managment of alcohol use XIII Center experiences for the interdisclipninary managment of alcohol use -- Management of Acute Alcohol Withdrawal: Practical Considerations and Role of Comorbidities Pathophysiology of Ethanol and Unexplained Observations Ethanol Metabolism Modulation of Alcohol-related Liver Disease by Obesity and Diabetes The Genetics Of Alcohol-Related Liver Disease (ALD) Mechanisms of Alcohol-related Liver Cirrhosis Alcoholic Fibrosis/Cirrhosis And Its Reversibility Alterations in Methionine Metabolic Pathway in the Pathogenesis of Alcohol-associated Liver Disease Mitochondria and Alcohol Hepatic Iron Overload in Heavy Drinkers: Molecular Mechanisms and Relation to Hemolysis and Enhanced Red Blood Cell Turnover Ethanol-Mediated Bone Marrow Toxicity And Impaired Erythropoiesis: Implications For Alcohol-Related Liver Disease The “Matrisome” and Alcohol-related Liver Disease MicroRNAs and Alcohol-associated Liver Disease Intestinal bacteria and bacterial endotoxin in the development and therapy of alcohol-related liver disease Microbiota and alcoholic liver disease Alcohol Potentiates HIV-induced Hepatotoxicity via Induction of Lysosomal Damage in Hepatocytes Pathophysiology Of Alcoholic Hepatitis: Emerging Role Of Enhanced Red Blood Cell Turnover#xa0; Diagnosis and Staging of Disease-severity in Symptomatic Alcoholic Hepatitis Management of Severe Forms of Alcoholic Hepatitis Mechanisms of Recovery from and Strategies for Survival of Severe Alcoholic Hepatitis and ACLF The Role of Liver Biopsy and Hepatic Venous Pressure Gradient for the Diagnosis and Prognosis of Severe Al ohol...
Keywords: Alkoholismus